The Relations of Locus of Control and Behavioral Approach and Inhibition Systems to General Health in Elderly Nursing Home Residents in Dubai - Majid Saffarinia; Atousa Mehdizadeh (University of Social Welfare & Rehabilitation Sciences, 2020)
Objectives: This article aimed to study the relations of locus of control and behavioral approach/inhibition systems to general health in elderly nursing home residents in Dubai.  Methods & Materials: In a cross-sectional study, 100 elderlies (60 male and 40 female) living in two nursing homes in Dubai were selected through categorized sampling. Participants completed the Locus of Control Scale (LCS), the Carver and Whitechr('39')s BIS/BAS Scales and the Goldbergchr('39')s General Health Questionnaire (GHQ). Data were analyzed by Pearson's correlation and multiple regression using SPSS software V. 21. Results: The Mean±SD of the ages of the men and women were 62.10±11.08 and 61.12±10.76, respectively. Also, the Mean±SD of internal locus of control, external locus of control, behavioral activation System (BAS), Behavioral Inhibition System (BIS) and general health were 4.32±3.21, 5.51±3.98, 29.66±5.79, 8.45±5.83, and 15.08±12.64, respectively. The results showed that all BAS subscales, BIS, and internal and external locus of control were related significantly to general health (P<0.01). BAS and its subscales correlated with depression (P<0.05, P<0.01). BIS and internal and external locus of control were connected to all subscales of general health (P<0.01).  Conclusion: Elderlies with external control and behavioral inhibition systems are at increased risk for mental health problems, while those with BAS and internal locus of control have a better mental health.